Application of integrated perturbation index and articulatory precision index in patients with spasmodic dysphonia - Sigal, Liliana; Gurlekian, Jorge A. (Revista de Investigación en Logopedia, 2014)
Spasmodic dysphonia -also called focal laryngeal dystonia- is a severe vocal disorder which presents nonvoluntary phonation breaks. This paper shows measurement results obtained by three indexes: 1) an integrated perturbation index (IPI), composed by four well known parameters: Jitter, Shimmer, Harmonic/Noise relation, and Cepstral peak amplitude and, 2) an articulatory precision index (IPA) for a population of patients with spasmodic dysphonia. These results are compared with a control set composed by patients with a laryngologist diagnose of mobile vocal folds with neither structural damages in the glotal mucosa, nor neurologic perturbations which could affect dynamics of the vocal folds. Results show clear differences between both groups for IPI and also for IPA. These indexes can be used as appropriated indicators to point out the lack of articulatory stability produced at the vocal resonators of patients with spasmodic dysphonia.
Keywords: Acoustic analysis; Integrated perturbation index; Spasmodic Dysphonia.